Supergirl. Book three - David, Peter (Peter Allen); Abnett, Dan; Lanning, Andy (DC Comics, 2017)
Linda Danvers is finally hitting her stride as Supergirl. Linda was hurtled into the world of crime-fighting when she was rescued from near death by fusing with Matrix, a protoplasmic version of Supergirl. She is getting better at balancing her old identity, including her relationships with friends and family, with her role as Leesburg's guardian angel.